Decision Analysis of Work Discipline and Employee Performance Variables Influenced by Motivation and Self-Efficacy Using the Path Analysis Method - Sjarifudin, Didin; Jumawan, Jumawan; Kurnia, Hibarkah (Program Pascasarjana Magister Teknik Industri Universitas Mercu Buana, 2024)
An organization that has a top-down type of command line wants its business to run smoothly, but sometimes there are obstacles due to differences in employee characteristics. Every organization has problems in improving the performance of its employees which are often affected by indiscipline at work. Work discipline is also problematic due to decreased employee confidence and work motivation. This research was conducted to create a research hypothesis regarding can work discipline and employee performance be influenced by motivation and self-efficacy. This research method uses a path analysis method whose data source is the results of questionnaire data collection involving several respondents from the West Java region of Indonesia. This research has found that the variables of self-efficacy and individual motivation do not partially influence discipline. However, these two variables have a significant influence on the discipline variable simultaneously at 39.4 percent. These two variables also influence employee performance. Then the combination of exogenous variables simultaneously has a significant influence on the performance variable of 67.9 percent. The contribution of this research is that every organization pays attention to employee character, self-efficacy, and motivation because it influences employee discipline and can improve employee performance in terms of productivity.